2019
DOI: 10.1039/c8nj04524k
|View full text |Cite
|
Sign up to set email alerts
|

A γ-Fe2O3-modified nanoflower-MnO2/attapulgite catalyst for low temperature SCR of NOx with NH3

Abstract: A novel mesoporous γ-Fe2O3-modified nanoflower-MnO2/attapulgite catalyst has been fabricated through a facile hydrothermal method and used for low temperature SCR of NOx with NH3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Attapulgite (ATP), which possessed abundant reserves in nature and was readily available, was a kind of water-containing magnesium-rich aluminum silicate clay mineral with a layered-chain structure. , Moreover, ATP owned large specific surface area and outstanding adsorption capability and was also a kind of environmentally friendly material, rendering it a promising prospect in becoming an appropriate catalyst carrier substitute. , Actually, ATP had indeed been used as a carrier to prepare NH 3 -SCR catalysts among several related studies. , Luo et al reported that TiO 2 -mixed ATP carrier supported γ-MnO 2 catalysts possessed nearly 100% NO x conversion within the scope of 200–300 °C . Zhou et al found that ATP supported γ-Fe 2 O 3 catalysts had a NO x conversion of 80–90% within 300–400 °C, while the NO x conversion of the ATP supported Mn–Fe oxide composite could be increased to nearly 100% within 250–300 °C .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attapulgite (ATP), which possessed abundant reserves in nature and was readily available, was a kind of water-containing magnesium-rich aluminum silicate clay mineral with a layered-chain structure. , Moreover, ATP owned large specific surface area and outstanding adsorption capability and was also a kind of environmentally friendly material, rendering it a promising prospect in becoming an appropriate catalyst carrier substitute. , Actually, ATP had indeed been used as a carrier to prepare NH 3 -SCR catalysts among several related studies. , Luo et al reported that TiO 2 -mixed ATP carrier supported γ-MnO 2 catalysts possessed nearly 100% NO x conversion within the scope of 200–300 °C . Zhou et al found that ATP supported γ-Fe 2 O 3 catalysts had a NO x conversion of 80–90% within 300–400 °C, while the NO x conversion of the ATP supported Mn–Fe oxide composite could be increased to nearly 100% within 250–300 °C .…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Moreover, ATP owned large specific surface area and outstanding adsorption capability and was also a kind of environmentally friendly material, rendering it a promising prospect in becoming an appropriate catalyst carrier substitute. 18,19 Actually, ATP had indeed been used as a carrier to prepare NH 3 -SCR catalysts among several related studies. 16,18−20 17 Zhou et al found that ATP supported γ-Fe 2 O 3 catalysts had a NO x conversion of 80−90% within 300−400 °C, while the NO x conversion of the ATP supported Mn−Fe oxide composite could be increased to nearly 100% within 250−300 °C.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[ 478 ] Among many catalysts, MnO 2 ‐based catalysts have attracted much attention due to their high SCR reaction activity. [ 175,201,479–483 ]…”
Section: Environmental Applicationsmentioning
confidence: 99%
“…117,118 For the pure MnO x catalyst, the ''synergistic poisoning'' of H 2 O and SO 2 accelerated the formation of metal sulfate and ammonium sulfate on the surface, which expedited the deactivation of the catalyst. 119 Choosing other metals as sacrificial sites to safeguard active MnO x species was also an effective way to enhance the resistance of catalysts to SO 2 . Investigations indicated that the modification of MnO x with Sb enormously ameliorated the resistance to SO 2 .…”
Section: Poisoning Mechanism and Poison-resistant Measures Of Somentioning
confidence: 99%